Patency of Multiple stents/Overlapping Stents in Single Artery Territory in Bangladeshi Patient: An Updated Single Center Experiences (Cardiovascular Journal, 2013)
Background: Coronary artery disease (CAD) in Bangladeshi population is diffuse in nature with small caliber arteries. Now a day, these are treated, by PCI with stent deployment, often multiple in a single coronary artery. However, long term data on In-stent re-stenosis (ISR) in multiple or overlapping stent in single coronary artery in these patients is not yet available. Therefore, the aim of our present study was to assess long-term outcome of stent patency or the development of ISR of varieties stent in single vessel territory. Methods: Patients were prospectively selected from, who underwent coronary angiogram at our hospital for further evaluation of their previous PTCA in the 3-36 months preceding the study for the quantifying period of 2007-2011. Total 51 patients (male: 42, Female: 9) who had multiple stents in one coronary artery were included in this study. Average age was Male: 57; Female:61. Average study period was 3.1 ± 2.4yrs. Results: Our results show that, among the total studied population 82.4% (42) were male and 17.6% (9) were female. Total 114 stent were deployed in 54 vessels of 51 patients. Territory wise distribution of deployed stent was LAD 52(45.6%), RCA 42 (36.8%) and LCX 20(17.5%). Stent used were BMS 45(39.5%), DES 69(60.5%). Re-look Coronary Angiogram (CAG) revealed that Significant ISR (ISR>60%) developed in BMS 8(17.8%) and DES 8(11.5%). Among the different DES the development of significant ISR were in Sirolimus 1(3.2%), Paclitaxel 4(16%), Everolimus 3 (30%). Conclusion: Our study has shown that deployment of multiple stents in a single artery territory (either separately or as overlapping) is safe and has reasonably lower degree of ISR, even when BMS was used. As a whole BMS shows higher degree of ISR than to DES for an average period of follow up of 3.1 yrs. DOI: http://dx.doi.org/10.3329/cardio.v5i2.14319 Cardiovasc. j. 2013; 5(2): 154-159